FRICTIONAL COEFFICIENT OF THE FLAT ROPE (Perner's Contacts, 2012)
The paper describing philosophy determination of the coefficient friction flat belt in face of steel tractive disk behind different service conditions. Flat belts are identified above all for maintenance-free application freight and passenger lift, where substitute chains and steel ropes.
Keywords: friction coefficient, flat rope